IMPLEMENTASI MODEL CONNECTED SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Nevi Novelita; Yanti Fitria; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to improve science learning outcomes with the Connected learning model. This research was conducted from March 5 2023 to April 5 2023. This research was conducted at SDN 23 Malabur with a population of 25 fourth grade elementary school students, with 15 males and 10 females. This research is a class action research (CAR). This connected research was carried out in 2 cycles consisting of 6 meetings. The results showed before PTK was 65%, and increased to 80% in cycle I and cycle II increased to 90%. The conclusion is drawn that the implementation of the connected model can help learning outcomes in Natural Sciences.